Electrochemical Detection of Lead Ion Based on a Peptide Modified Electrode. Issue 5 (10th December 2015) - Lin, Meng; Cho, MiSuk; Choe, Woo‐Seok; Lee, Youngkwan
Abstract: A novel biosensor harnessing a peptide layer which has specific affinity to lead ion proved to be highly effective for electrochemical analysis of lead ions. The peptide modified electrode was used for the electrochemical analysis of various trace metal ions by square wave voltammetry. Compared to the other ions investigated, the peptide modified electrode was found to be highly selective to Pb 2+ in the range of 50–700 nM. Furthermore, the biosensor exhibited a high reusability and good spike recovery in the tap water containing various concentration of Pb 2+ . Abstract :